2022
DOI: 10.1111/jop.13301
|View full text |Cite
|
Sign up to set email alerts
|

Immunoexpression of oral brush biopsy enhances the accuracy of diagnosis for oral lichen planus and lichenoid lesions

Abstract: Background: This study assessed the efficacy of using oral liquid-based brush cytology (OLBC) coupled with immunostained cytology-derived cell-blocks, quantified using machine-learning, in the diagnosis of oral lichen planus (OLP).Methods: Eighty-two patients diagnosed clinically with either OLP or oral lichenoid lesion (OLL) were included. OLBC samples were obtained from all patients before undergoing surgical biopsy. Liquid-based cytology slides and cell-blocks were prepared and assessed by cytomorphology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Therefore, our study employed machine learning for objective and reproducible assessment of IHC data. This approach has been validated previously while defining the ROI as the total epithelial thickness of the WSI minimising human intervention 19 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, our study employed machine learning for objective and reproducible assessment of IHC data. This approach has been validated previously while defining the ROI as the total epithelial thickness of the WSI minimising human intervention 19 …”
Section: Discussionmentioning
confidence: 99%
“…This approach has been validated previously while defining the ROI as the total epithelial thickness of the WSI minimising human intervention. 19 The angiogenic switch is a discrete step that can commence at different stages during the carcinogenesis process. 14 Currently, however, there is no reliable tool to detect the occurrence of the angiogenic switch.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research in molecular pathology has identified thousands of biomarkers related to HNSCC. While promising outcomes have been reported when employing molecular biomarkers to detect and diagnose oral cancers and potentially malignant oral disorders [ 11 , 12 ], the reliability of prognostic biomarkers in HNSCC is uncertain due to the unsatisfactory quality levels of relevant studies and the heterogeneity of reporting [ 13 ]. Liquid biopsies, however, are reliable sources of certain body-fluid-based biomarkers, such as cell-free nuclear DNA (cf-nDNA) and cell-free mitochondrial DNA (cf-mtDNA) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%